Description of the use of contrast‐enhanced ultrasonography in four dogs with pancreatic tumours. (1st November 2013) - Vanderperren, K.; Haers, H.; Van der Vekens, E.; Stock, E.; Paepe, D.; Daminet, S.; Saunders, J. H.
<x xml:space="preserve">Abstract</x> Canine pancreatic tumours are rare compared to human medicine and the detection and differentiation of pancreatic neoplasia is challenging with B‐mode ultrasonography, which often leads to late clinical diagnosis and poor prognosis. This case report describes the findings of contrast‐enhanced ultrasonography in four dogs with pancreatic adenocarcinoma or insulinoma. B‐mode ultrasonography of the pancreas revealed a hypoechoic nodule in three dogs and heterogenous tissue in one dog. Contrast‐enhanced ultrasonography was able to differentiate between two tumour types: adenocarcinomas showed hypoechoic and hypovascular lesions, whereas insulinomas showed uniformly hypervascular lesions. Contrast‐enhanced ultrasonography findings were confirmed by cytology and/or histopathology. The results demonstrated that contrast‐enhanced ultrasonography was able to establish different enhancement patterns between exocrine (adenocarcinoma) and endocrine (insulinoma) tumours in dogs.